The Effect of Attention Training Techniques on The Attention and Performance of Taekwondo Athletes - Ersa Makhroja; Komarudin Komarudin; Nida'ul Hidayah; Geraldi Novian (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Optimal performance in various fields, such as sports, is highly dependent related to a person’s capacity to preserve consistent focus and attentiveness, especially in the psychological aspect.The study seeks to explore and assess the effectiveness generated through attention training techniques on imploving concentration and performance among taekwondo athletes. The study adopted an approach involving one group assessed both prior to and following the treatment was implemented for 10 sessions, scheduled thrice a week, involving 12 taekwondo athletes. A questionnaire derived from the TAIS (The Test of Attentional and Interpersonal Test) containing seven measurement dimensions serves as primary instrument of this study, then the calculation of athlete performance will use medal data before and after treatment, adjusted to the World Taekwondo Federation competition grade. The study’s data will be analyzed through SPSS, highlighting a considerable enhacement in taekwondo athletes’ performance and focus through the application of attention training techniques from Cirebon. The results demonstrate that attention training techniques produce a meaningful and beneficial impact on both the attention and performance of taekwondo athletes. Further studies are needed to apply this research to a broader and more diverse population and to examine the longer term effects of attention training techniques